A Real-Time Capsule-Based Design Model to Realize AUV Controllers - Ngo, Van Hien (Old Journal, 2017)
This paper brings out a real-time capsule model of Autonomous Underwater Vehicles (AUVs) controllers, which is based on the real-time Unified Modeling Language (UML) with a Domain-Specific Language (DSL) of Modeling and Analysis of Real-Time and Embedded Systems (MARTE) in order to intensively carry out the whole of development lifecyle for the AUV’s control system. The main study is stepwise carried out as follows: the AUV dynamics together with control structure are firstly adapted for developing entirely an AUV controller. The use-case model combined with an implementable functional block diagram and the Extended Kalman Filter (EKF) algorithm are then specialized to closely gather the requirements analysis of control. The specializations of real-time UML/MARTE’s features combined with the capsule evolution of timing concurrency are next realized to precisely design structures and behaviors for the controller. The detailed design model is then converted into the implementation model by using open-source platforms in order to quickly simulate and realize this controller. Finally, a trajectory-tracking controller, which permits a miniature unmanned submarine possessing a torpedo shape to autonomously reaches and follows a horizontal planar reference trajectory, was completely deployed and tested.